Studi Cross Sectional Faktor-faktor yang Berhubungan dengan Perilaku Personal Hygiene pada Siswa Kelas IV dan V di SDN Jelambar 03 Pagi Jakarta Barat Tahun 2025: Analisis Kuantitatif tentang Pengetahuan, Sikap, dan Faktor sosial terhadap Perilaku Personal Hygiene Siswa - ali, salma (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2025)
Elementary school children are at a stage of development that is the early stage of forming healthy living habits, so it is important to understand the factors that influence their personal hygiene behavior. This study aims to determine the factors associated with personal hygiene behaviorin fourth and fifth grade students at SDN Jelambar 03 Pagi. This study used a quantitative method with a cross-sectional approach, and data were collected through questionnaires and observation. Data analysis consisted of univariate and bivariate analysis with the Chi-square statistical test. The study population consisted of all fourth and fifth grade students at SDN Jelambar 03 Pagi, and the sample size was 110 students using total sampling technique. The results of the study describe that hygiene behavior (67.3%), good knowledge (61.8%), positive attitudes (58.2%), supportive parental roles (76.4%), supportive teacher roles (60.9%), and supportive peer roles (65.5%). The analysis results showed a relationship between knowledge (pvalue=0.047), attitude (pvalue=0.025), parental role (pvalue=0.017), teacher role (pvalue=0.024), peer role (pvalue=0.010). Based on the research results, it is known that there is an influence between knowlwdge, attitude, parental role, teacher role, and peer role on the personal hygiene behavior of students at SDN Jelambar 03 Pagi. Therefore, schools are expected to provide education and examples and to supervise personal hygiene. Keywords: Behavior, elementary students, personal hygiene